EMPLOYEE PERFORMANCE ASSESSMENT USING THE 360 DEGREE FEEDBACK METHOD AT PT NUSANTARA SEBELAS MEDIKA - Adi Purnomo; Hadi Sunaryo; Agus Salim (International Journal of Cultural and Social Science, 2025)
This study explores the implementation of a 360-degree feedback performance appraisal system at PT Nusantara Sebelas Medika to enhance employee evaluation. Traditional appraisal systems often suffer from bias and limited perspectives, primarily focusing on supervisors and peers. This study applies the 360-degree feedback method, involving evaluations from supervisors, peers, subordinates, self-assessments, and customers. Data were collected from 10 respondents using purposive sampling. Results indicate that this method improves objectivity, provides comprehensive feedback, and helps employees identify their strengths and weaknesses. The findings underscore the method’s potential for fostering a transparent, fairer appraisal system and enhancing employee motivation and organizational performance. This study contributes to the academic literature on performance appraisal systems, particularly within the healthcare sector, by demonstrating the benefits of multi-source feedback in performance evaluation.